Kesegaran Jasmani dan Ketahanan Diri Remaja Blitar - Gideon Bayu Hariyawan; Anangga Widya Pradipta; Nurcholis Istiawan; Agung Yuda Aswara (SPRINTER: Jurnal Ilmu Olahraga, 2026)
Adolescents are a developmental group vulnerable to various biological, psychological, and social pressures, making resilience an important adaptive resource for psychological well-being and optimal development. On the other hand, physical fitness not only plays a role in maintaining physical health but also has the potential to support adolescents’ psychological capacity. This study aimed to examine the levels of physical fitness and resilience among adolescent girls in Blitar, investigate their differences based on school type, and identify the relationship between the two variables. This study employed a quantitative approach with a comparative-correlational design. A total of 1,881 female upper secondary school students in Blitar (1,139 senior high school students and 742 vocational high school students) were involved as participants through snowball sampling. Data were collected using the Perceived Physical Fitness Scale and the Resilience Scale for Teenagers, and were analyzed using One-Sample t-tests, Independent Samples t-tests, and Pearson correlation. The findings showed that the mean score of physical fitness (M = 36.97) was below the established threshold of 40.9 (p < .001), whereas the mean score of resilience (M = 45.39) was above the threshold of 42.1 (p < .005). No significant differences were found in physical fitness (p = .081) or resilience (p = .737) based on school type. Furthermore, a positive and significant relationship was found between physical fitness and resilience (r = .393; p < .05). This study concludes that the physical fitness of adolescent girls in Blitar still requires attention, although their resilience has developed relatively well. These findings highlight the importance of strengthening physical fitness as part of a more integrative strategy for adolescent health development.